Tonic Investigation Concept of Cervico-vestibular Muscle Afferents - Dorn, Linda Josephine; Lappat, Annabelle; Neuhuber, Winfried; Scherer, Hans; Olze, Heidi; Hölzl, Matthias (International Archives of Otorhinolaryngology, 2017)
Introduction Interdisciplinary research has contributed greatly to an improved understanding of the vestibular system. To date, however, very little research has focused on the vestibular system's somatosensory afferents. To ensure the diagnostic quality of vestibular somatosensory afferent data, especially the extra cranial afferents, stimulation of the vestibular balance system has to be precluded.Objective Sophisticated movements require intra- and extra cranial vestibular receptors. The study's objective is to evaluate an investigation concept for cervico-vestibular afferents with respect to clinical feasibility.Methods A dedicated chair was constructed, permitting three-dimensional trunk excursions, during which the volunteer's head remains fixed. Whether or not a cervicotonic provocation nystagmus (c-PN) can be induced with static trunk excursion is to be evaluated and if this can be influenced by cervical monophasic transcutaneous electrical nerve stimulation (c-TENS) with a randomized test group. 3D-video-oculography (VOG) was used to record any change in cervico-ocular examination parameters. The occurring nystagmuses were evaluated visually due to the small caliber of nystagmus amplitudes in healthy volunteers.Results The results demonstrate: no influence of placebo-controlled c-TENS on the spontaneous nystagmus; a significant increase of the vertical nystagmus on the 3D-trunk-excursion chair in static trunk flexion with cervical provocation in all young healthy volunteers (n = 49); and a significant difference between vertical and horizontal nystagmuses during static trunk excursion after placebo-controlled c-TENS, except for the horizontal nystagmus during trunk torsion.Conclusion We hope this cervicotonic investigation concept on the 3D trunk-excursion chair will contribute to new diagnostic and therapeutic perspectives on cervical pathologies in vestibular head-to-trunk alignment.
Keywords: vertical nystagmus; cervical nystagmus; cervical vertigo; TENS; neck torsion test; trunk excursion chair